Manajemen Talenta dan Peningkatan Kinerja Aparatur Sipil Negara: Suatu Kajian Literatur pada Sektor Publik Indonesia - Ikhwal; Waode Sunaini; Maudhy Satyadharma; La Ode Muhammad Ichwan Sjachrawy; Taziruddin (Journal of Economics, Management, and Accounting, 2025)
This study examines the implementation of talent management as a strategic approach to improving civil servant performance in Indonesia’s public sector. Employing a literature review and narrative analysis, it synthesizes recent studies and national reports from 2021–2025. The findings indicate that the Indonesian government has strengthened merit-based human resource governance through digital systems such as SIASN and e-SKP, alongside the establishment of regional talent pools. Nevertheless, disparities persist due to leadership rotation, limited competency budgets, and inconsistent data integration. Managerial capacity, institutional readiness, and leadership commitment emerge as the main determinants of success. The study emphasizes that sustainable talent management requires aligning digital transformation, performance-based evaluation, and competency development within organizational strategy. When effectively implemented, talent management not only enhances employee performance but also drives bureaucratic efficiency and accountability. Thus, it functions as a strategic pillar supporting Indonesia’s ongoing public sector reform and administrative modernization.